1974
DOI: 10.1111/j.1399-3011.1974.tb02407.x
|View full text |Cite
|
Sign up to set email alerts
|

The Enniatin Ionophores. Conformation and Ion Binding Properties

Abstract: The ability of enniatins to bind alkali metal, alkaline earth metal and certain transition metal ions in solution has been investigated. The complexes have been shown to form in 1:1, 2:1 and 3:2 macrocycle:cation ratios; their stability constants have been determined, and the conditions favoring their formation have been established. The enniatins were shown to be complexones of very wide spectrum, displaying low metal ion selectivity in alcoholic solutions. Two basic spatial forms, the non‐symmetric N3 form (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(43 citation statements)
references
References 42 publications
3
40
0
Order By: Relevance
“…Due to ionophoric properties, enniatins have been shown to have insecticidal activity as well as antimycobacterial activity, one of the most potent being enniatin B (Ovchinnikov et al, 1974;Lifson et al, 1984;Visconti et al, 1992;Doebler, 2000;Firáková et al, 2007). They inhibit various enzymes, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Due to ionophoric properties, enniatins have been shown to have insecticidal activity as well as antimycobacterial activity, one of the most potent being enniatin B (Ovchinnikov et al, 1974;Lifson et al, 1984;Visconti et al, 1992;Doebler, 2000;Firáková et al, 2007). They inhibit various enzymes, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This was based on a significant depolarisation of the mitochondrial membrane potential, which is an important step to trigger programmed cell death, after 48 h PF1022A treatment with 10 µM [50]. Moreover, several characteristics of programmed cell death like cell shrinkage, chromatin condensation and apoptotic body formations were observed after 48 h drug treatment with 10 µM PF1022A.…”
Section: Discussionmentioning
confidence: 99%
“…This strongly suggests that PF1022A is a potential channelforming ionophore. Moreover, formation of a sandwich complex can be postulated similar to the cyclohexadepsipeptides beauvericin [49] and enniatin [50]. Through such PF1022A-induced membrane spanning pores, ions are able to diffuse at both directions following their electrochemical gradient.…”
Section: Discussionmentioning
confidence: 99%
“…They appear in nature as mixtures of cyclic depsipeptides -the main variants are enniatins A, A1, B, and B1, together with minor amounts of enniatins C, D, E, and F. Enniatins function as ionophores by their incorporation into the cellular membrane to form dimeric structures. They transport monovalent ions across the membrane, especially the mitochondrial membranes, affecting oxidative phosphorylation uncoupling [5][6][7][8]. It has been demonstrated that enniatins have a cytotoxic effect on human cancer cells [9].…”
Section: Introductionmentioning
confidence: 99%